Associação de betabloqueadores e treinamento físico na insuficiência cardíaca de camundongos - Vanzelli, Andréa Somolanji (2010)
BACKGROUND: Currently there are several types of interventions for the treatment of heart failure (HF). Among these are beta-blocker therapy (BB) and physical training (PT). However, the effects of the combination of these therapies are poorly studied. OBJECTIVE: To investigate the effects of BB treatment with metoprolol (M) and carvedilol (C) associated with PT in mice with HF. METHODS: We used a genetic model of sympathetic hyperactivity-induced heart failure in mice. Initially, we divided the HF animals into three groups: sedentary (S); trained (T); treated with M (138 mg/kg) (M); or C (65 mg/kg) (C). In the second part, we divided the groups into three subgroups: sedentary (S); trained and treated with M (TM); and trained and treated with C (CT). The PT consisted of aerobic training on a treadmill for 8 weeks. Exercise tolerance was assessed by maximal graded test, and fractional shortening (FS) was assessed by echocardiography. Cardiomyocyte diameter and collagen volume fraction were evaluated by histological analysis. Data were compared by one way ANOVA and post hoc Duncan test. The significance level was set at p < 0.05. RESULTS: As to FS and cardiac remodeling, we found that, in isolation, T, M, and C showed an improvement of the variables analyzed. As to therapy combination, after the intervention period, we observed an increase in exercise tolerance in MT and CT (43.0% and 33.0% respectively). There was also a reduction in cardiomyocyte diameter (10.0% and 9.0% respectively) and in collagen volume fraction (52.0% and 63.0%) after the intervention. However, only CT significantly improved FS. CONCLUSION: The association of PT with M or C therapies provided benefits on cardiac function and remodeling in HF mice.